Tests of robustness of GMM speaker verification in VoIP telephony - Staroniewicz, Piotr (Archives of Acoustics, 2007)
The paper presents the scores of the GMM (Gaussian Mixture Models) based speakerverification system for speech signal transmitted in VoIP (Voice over IP) telephony conditions.The speaker verification problem was partly solved over traditional PSTN networks(Public Switched Telephone Network), however nowadays it is also important to assess howspecific distortions of VoIP transmission influence the speaker verification scores. As a referencedatabase XM2VTS (Extended multi Modal Verification for Teleservices and Securityappliations Data Base) containing English speech (strings of digits) was applied. Three coderdegradations (PCM, G.711A and G.723.1) and three network conditions were examined invarious configurations to estimate the influence of each, coding and transmission degradationfor the final verification scores.